PENGARUH TATA KELOLA PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN SAHAM PUBLIK DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia 201 - Arif Rachman Susanto (AKT 16 UMY 007, 2016)
The purpose of this study was to know the influence of good corporate governance, institutional ownership, public ownership and leverage to the earnings management. The study focused on manufacturing companies listed in Bursa Efek Indonesia during 2011-2014. The study used purposive sampling method in order to collect the sample. Population in this study was to all manufacturing companies listed in Bursa Efek Indonesia during 2011-2014. Based on certain criteria, there were 50 of 151 manufacturing companies that matched with the sample. The statistical method used in this study was mutiple regression. The result of this study showed that good corporate governance has the negative (0,108) and un-significant (0,914) effect to the earnings management. Institutional ownership has the negative -3,268) and significant (0,001) effect to the earnings management. Public ownership has the negative (-4,179) and significant (0,000) effect to the earnings management. Leverage has the positive (1,155) and un-significant (0,249) effect to the earnings management. The goodness of fit testing showed that good corporate governance, institutional ownership, public ownership and leverage were influenced to the earnings management with count F value 6.118 and significant 0,000. The adjusted ð‘…2 was 0,093, that showed the influence of good corporate governance, institutional ownership, public ownership and leverage to the earnings management at 9,3%. Keywords: Earnings management; good corporate governance; institutional ownership; public ownership; leverage